Pengaruh Corporate Identity terhadap Keputusan Menggunakan Produk Simpanan Mudharabah Khusus Pelajar di Baitul Maal Wat Tamwil (BMT) Madani - Fitriyah Ningsih; Prayudi Setiawan Prabowo (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
The purpose of this study was to analyze whether there is an influence between Corporate Identity on the decision to use mudharabah savings products specifically for students in BMT Madani Sepanjang, Sidoarjo. This type of research is associative quantitative. The population used as many as 400 people, while the sample used as many as 200, the determination of the data using the Non Probability Sampling technique. The data collection method using interview, observation and questionnaire. The data analysis method uses simple linear analysis. The results obtained indicate that there is a positive and significant influence between Corporate Identity on the decision to use mudharabah savings products specifically for students. The influence of the Corporate Identity variable on the decision variable is 36.8%, while 63.2% is influenced by other variables.